Romellia is congeneric with Togninia, and description of Conidiotheca gen. nov. for one species of this genus with polysporous asci - Réblová, Martina; Mostert, Lizel (Mycological research, 2007)
During a continued survey of fungi accommodated in the Calosphaeriales, we observed that the genus Romellia is morphologically heterogeneous. Historically, four species were placed in the genus. Romellia was introduced for taxa with globose, dark, superficial, papillate perithecia, a paraphysate centrum, and octosporous asci containing eight allantoid, hyaline ascospores. The type species, R. vibratilis, was revised in our study, and its freshly collected material was cultured. The anamorph obtained in vitro matches the generic concept of the hyphomycete genus Phaeoacremonium, the anamorph of Togninia. The phylogenies inferred from newly obtained sequences of LSU rDNA, beta-tubulin, and actin of R. vibratilis revealed that the species is congeneric with Togninia (Togniniaceae) and represents a good species. Revision of type and herbarium material of other Romellia species confirmed they are not congeneric with Togninia. Romellia tympanoides possesses immersed, subglobose perithecia with sessile asci containing eight ascospores, which during maturation produce ascoconidia filling the entire ascus. This maturation process represents a new kind of apparent polyspory known in the ascomycetes. We introduce a new genus, Conidiotheca, and a new combination for R. tympanoides. The species is compared with the genera Barrina and Tympanis. The relationships of two other Romellia species, R. ambigua and R. cornina, lie with Wegelina and Jattaea of the Calosphaeriales.
Keywords: DNA fungální; DNA, Fungal; druhová specificita; DNA, Ribosomal; Fungi; Phylogeny; Netherlands; fungální proteiny; aktiny; Nizozemsko; houby; Tubulin; Ascomycota; Plant Bark; fylogeneze; kůra rostlin; tubulin; Species Specificity; ribozomální DNA; Actins; Fungal Proteins